The impact of care environment on the mental health of orphaned, separated and street-connected children and adolescents in western Kenya: a prospective cohort analysis. Issue 3 (31st March 2021) - Omari, Felicita; Chrysanthopoulou, Stavroula A; Embleton, Lonnie E; Atwoli, Lukoye; Ayuku, David O; Sang, Edwin; Braitstein, Paula
Abstract : Introduction: The effect of care environment on orphaned and separated children and adolescents' (OSCA) mental health is not well characterised in sub-Saharan Africa. We compared the risk of incident post-traumatic stress disorder (PTSD), depression, anxiety and suicidality among OSCA living in Charitable Children's Institutions (CCIs), family-based care (FBC) and street-connected children and youth (SCY). Methods: This prospective cohort followed up OSCA from 300 randomly selected households (FBC), 19 CCIs and 100 SCY in western Kenya from 2009 to 2019. Annual data were collected through standardised assessments. We fit survival regression models to investigate the association between care environment and mental health diagnoses. Results: The analysis included 1931 participants: 1069 in FBC, 783 in CCIs and 79 SCY. At baseline, 1004 participants (52%) were male with a mean age (SD) of 13 years (2.37); 54% were double orphans. In adjusted analysis (adjusted HR, AHR), OSCA in CCIs were significantly less likely to be diagnosed with PTSD (AHR 0.69, 95% CI 0.49 to 0.97), depression (AHR 0.48 95% CI 0.24 to 0.97), anxiety (AHR 0.56, 95% CI 0.45 to 0.68) and suicidality (AHR 0.73, 95% CI 0.56 to 0.95) compared with those in FBC. SCY were significantly more likely to be diagnosed with PTSD (AHR 4.52, 95% CI 4.10 to 4.97), depression (AHR 4.72, 95% CI 3.12 to 7.15), anxiety (AHR 4.71, 95% CI 1.56 to 14.26) and suicidality (AHR 3.10, 95% CI 2.14 to 4.48) compared with those in FBC. Conclusion: OSCA living in CCIs in this setting were significantly less likely to have incident mental illness, while SCY were significantly more, compared with OSCA in FBC.